Metal bioavailability in aquatic systems— beyond complexation and competition - Fortin, Claude (Frontiers in Environmental Chemistry, 2024)
Metal bioavailability in solution is mostly driven by two factors: complexation and competition. The first factor, complexation, contributes to decrease the overall reactivity of the metal by reducing the activity of the free metal ion, which is known as the common denominator of metal reactions involving either dissolved ligands or surface functional groups (abiotic or biotic). Ubiquitous in natural ecosystems, natural organic matter is, for several metals, the most important metal complexing ligand. The second factor, competition, contributes to decrease the availability of biotic ligands involved in the membrane transport of metals from the bulk solution to the intracellular medium. In freshwater systems, proton and hardness cation concentrations are the main parameters potentially modulating metal bioavailability. The above reflects the current accepted paradigm. In this paper, two knowledge gaps are identified: i) the role of natural organic matter other than metal complexation that may lead to an increase in metal bioavailability; and ii) the effects of multiple metals other than competition that may trigger biological feedback mechanisms which may, in turn, alter biotic ligand binding properties. More research efforts are needed to decipher the extent of these overlooked potential effects and to improve the predictability of metal bioavailability.